Jual Beli Menggunakan Vending Machine Persepektif Hukum Ekonomi Syariah - Utami, Sri; Fikriawan, Suad; Nafiah, Nafiah (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Modern devices known as vending machines are being developed today and are used in buying and selling operations. Because the buyer only makes transactions with the machine acting as the seller, there is actually no participation between the seller and the customer when using a vending machine. In addition, there is no negotiation process to reach an agreement.This research tries to ascertain the position of Sharia Economic Law regarding the rules governing the buying and selling of vending machines. A case study research methodology was used in this investigation. Efforts to describe research into vending machine buying and selling studies are in accordance with the descriptive nature of this research. Therefore, based on the description of this study, it will show the regulations governing the buying and selling of vending machines from the perspective of sharia economic law. This research collects data through documentation and interviews. According to research findings, the law of buying and selling automatic vending machines is permitted as long as they comply with the rules and conditions of buying and selling, such as the agreement and willingness of the parties. Conditions and harmony Buyers and automated machines do this through their actions or signals. The guiding values ​​of Islamic law, namely al-'ilah (justice), al-hurriyah (freedom), al-mas'ûliyah (accountability), honesty and truth have been upheld in buying and selling. Using a description of legal guidelines. If difficulties arise in vending machine buying and selling transactions which result in buyers experiencing losses, for example money being misappropriated, then according to Islam vending machines should be avoided.